Dialectics and Madurese Language Accent in the Perspective of Psycholinguistic and Sociolinguistic - Fudhaili, Achmad (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2024)
This research aims to reveal and examine the variety of Madurese dialects found in 4 districts in Madura (Bangkalan, Sampang, Pamekasan, and Sumenep) and their factors, starting from acquisition factors to surrounding environmental factors, as well as their influence on a person's attitude patterns. The research method used is a qualitative research method with a phenomenological approach. The research subjects that will be studied are the Madurese people in general from each district. The data collection instrument used structured interviews involving 3 people from each district and sources from the literature. The data analysis technique used by researchers is qualitative descriptive. Data analysis includes data condensation, data presentation, and drawing conclusions. Based on research results, the diversity of Madurese dialects based on psycholinguistic and sociolinguistic studies is formed through the acquisition factor of Madurese language diversity in the form of vocabulary (dialect) by the human mental lexicon obtained by their social environment. Meanwhile, the diversity of the Madurese language accent is formed from various factors, including cultural, geographical, and social class factors, which influence their attitude patterns.